1999
DOI: 10.1063/1.480161
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic intermolecular interactions in van der Waals and hydrogen-bonded complexes: What can we get from density functional calculations?

Abstract: Articles you may be interested inPerformance of dispersion-corrected double hybrid density functional theory: A computational study of OCShydrocarbon van der Waals complexes Computational and experimental investigation of intermolecular states and forces in the benzene-helium van der Waals complex Comment on "Anisotropic intermolecular interactions in van der Waals and hydrogen-bonded complexes: What can we get from density-functional calculations?" [J.The applicability of various density functional theory ͑DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 66 publications
(38 reference statements)
1
63
0
Order By: Relevance
“…1 and 2 for GGA and LDA functionals, respectively. Similar comparisons of KSCED ͑GGA and LDA͒ results with ab initio reference data 25 were made for seven other structures of the water dimer. Opposite to the previous set of structures, these geometries do not correspond to stationary points on the potential-energy surface but are the structures generated via rotation ͑ = −52°, −22°, −8°, 38°, 68°, 98°, and 128°͒ of one of the water molecules keeping the inter- The reference data used for two water dimer sets is of a different quality.…”
Section: A Ksced Interaction Energies At Equilibrium Geometriesmentioning
confidence: 52%
“…1 and 2 for GGA and LDA functionals, respectively. Similar comparisons of KSCED ͑GGA and LDA͒ results with ab initio reference data 25 were made for seven other structures of the water dimer. Opposite to the previous set of structures, these geometries do not correspond to stationary points on the potential-energy surface but are the structures generated via rotation ͑ = −52°, −22°, −8°, 38°, 68°, 98°, and 128°͒ of one of the water molecules keeping the inter- The reference data used for two water dimer sets is of a different quality.…”
Section: A Ksced Interaction Energies At Equilibrium Geometriesmentioning
confidence: 52%
“…Moreover, they reported that the CO 2 /pyridine complex was more strongly bound by 5.6 kJ/mol than the CO 2 /triethylamine complex [35]. However, the calculations performed by Meredith et al may be in error because DFT is known not to be accurate for weakly bound systems because the electron correlation treatment in B3LYP has the wrong long-range behavior, and therefore cannot capture the correct van der Waals dispersion interactions [36]. Hence, for supramolecular systems in which the binding is dominated by dispersive interactions, both the geometries and binding energies may be in error.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that steric repulsion of the ethyl groups in triethylamine causes the binding energy of the CO 2 -triethylamine complex to be weaker than that of the CO 2 -pyridine complex, whereas the planar structure of pyridine leads to less steric hindrance, allowing the nitrogen atom to be closer to the carbon of CO 2 . The density functional theory formalism used by Meredith et al to compute the CO 2 -amine interactions [35] lacks an accurate description of electron correlation effects that give rise to van der Waals interactions [36], which are expected to dominate the CO 2 -amine interaction; therefore the binding energies and perhaps even the geometries they report may be substantially in error. Furthermore, contrary to the results by Meredith et al, our ab initio calculations, reported in this paper, indicate that interactions between CO 2 and tert-amines are highly favorabledeven stronger than CO 2 -carbonyl interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The scaling factor s r, 6 for the cutoff radii in the damping function used in conjunction with this functional has been set to a value of s r, 6 = 1.0.…”
Section: Correlation Energies From the Localised Weighted Exchangementioning
confidence: 99%
“…1) that are based on the local density approximation or the generalised gradient approximation (GGA) are unable to describe the important long-range correlation interactions between molecular systems that are not bound by covalent bonds. [2][3][4][5][6][7][8][9] The reason for this stems from the fact that these functionals contain exchange-correlation energy densities which are only locally dependent on the electron density and its derivatives and therefore lack the capability to describe interactions of molecular regions that are spatially separated. More recent (semi-local) hybrid meta GGA's (Refs.…”
Section: Introductionmentioning
confidence: 99%